Developing a strategy for fisheries-based tourism potential on Jolosutro beach, Blitar Regency, East Java Province - Andini Risfandini; Fitria Earlike Anwar Sani (Jurnal Pariwisata Pesona, 2024)
The development of infrastructure in the form of the South Crossline provides positive impacts on the regions it passes through, including Blitar Regency in East Java Province. The South Crossline in Blitar Regency passes through several exotic beaches, one of which is Jolosutro Beach. Jolosutro Beach is already well-known as a religious tourist destination for Hindu devotees. During significant moments such as the Melasti Ceremony and the Tabur Kasanga Ceremony, this beach is crowded with Hindu devotees and domestic tourists, reaching up to 15,000 people. At other times, the beach is visited by around 500 visitors, and the number increases during holidays. To enhance the tourism appeal in the Jolosutro area, development is needed to integrate tourism activities through fisheries-based initiatives. This study utilizes the SWOT analysis method to identify several priority strategies that can be implemented to increase tourist visits and improve the income of the local community. The strategies for developing fisheries-based tourism potential in Jolosutro Beach, Blitar Regency, include: creating branding through the identification of cultural and fisheries tourism potential that reflects local wisdom values, establishing destination management governance, providing tourism human resources training, and providing funding support for fishermen and micro and small-scale businesses (CSR).Â Â